2014
DOI: 10.1159/000369825
|View full text |Cite
|
Sign up to set email alerts
|

Biobanking Trends, Challenges, and Opportunities

Abstract: Objectives: To review the different interests and needs of industry and academic users of human biomaterials. Methods: A review of the current literature and interviews with involved parties. Questionnaires were e-mailed to assess current attitudes towards biobanking and opinions of trends and implications for the future. The organisations included commercial biobanks, charitable foundations, academic biobanks, and hospital sites. Results: Biobanks have the potential to have a critical impact across several in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Those who never had exposure to research ethics training have a lack of knowledge and awareness on the types of informed consent, ethical issues, and legal consequences. Despite the arguments on the types of informed consent and its ethical and legal aspects in biobanking (Kegley 2004;Khan et al 2014;Mackenzie 2014), 44% of the informants in this study who were involved directly in biobanking research were unsure of other types of informed consent in biobanking and its ethical and legal consequences. This study showed that although the informants were involved directly in biobanking research, experience alone may not be sufficient to help them understand and be aware of the ethical and legal implications in biobanking.…”
Section: Informants' Background and Trainingmentioning
confidence: 74%
“…Those who never had exposure to research ethics training have a lack of knowledge and awareness on the types of informed consent, ethical issues, and legal consequences. Despite the arguments on the types of informed consent and its ethical and legal aspects in biobanking (Kegley 2004;Khan et al 2014;Mackenzie 2014), 44% of the informants in this study who were involved directly in biobanking research were unsure of other types of informed consent in biobanking and its ethical and legal consequences. This study showed that although the informants were involved directly in biobanking research, experience alone may not be sufficient to help them understand and be aware of the ethical and legal implications in biobanking.…”
Section: Informants' Background and Trainingmentioning
confidence: 74%
“…The potential for public–private collaboration in the field of biobanking is underused, even though there is a demand from companies for samples, data, and research ideas. 12 , 79 This lack of cooperation is also undesirable from a societal point of view, as the private sector is generally needed to bring new innovations to the market and create impact for patients. Academic researchers and biobanks may benefit from public–private partnerships through joint publications, enhanced reputation, and visibility, additional funding and the exchange of knowledge.…”
Section: Recommendations For Creating the Right Conditions For Sustainable Biobankingmentioning
confidence: 99%
“… 10 , 11 This has provided a stimulus for increased access to fixed tissues in clinical archives for retrospective studies. 12 , 13 At the same time, there has been a recent increased demand for prospectively collected fresh tissue and blood samples, 14 , 15 possibly attributable to the increased interest in the function of the immune system in health research. Collectively these trends have led to diminished demand for frozen biospecimens in biobank inventories ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%